Peran Perangkat Desa dalam Sektor Pajak Bumi dan Bangunan di Kecamatan Tulangan Kabupaten Sidoarjo - Susanti, Yaniar Larasita; Afandi, Andik (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2013)
The purposes of this research were to explain the role and effort are done by officers in the Tulangan Sub-district in collecting land and building tax (PBB), to explain the factors which encourage and inhibit the performance of officers in sub-district tulangan in collecting PBB. This study used descriptive research with qualitative analysis as it describe how tax of land and building are collected by officers in Tulangan Sub-district as well as factors that drives and hinder the duty of tax collector. The result of this research showed that the role of officers in land and building tax sector was merely as tax collector without having the role of motivator toward citizens to pay the tax, so that public participation as land and building taxpayers is low. Many people were still not punctual in paying off their taxes.